2011
DOI: 10.1111/j.1468-1293.2011.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Major but differential decline in the incidence of Staphylococcus aureus bacteraemia in HIV‐infected individuals from 1995 to 2007: a nationwide cohort study*

Abstract: all Danish HIV-infected individuals (n 5 4871) and population controls (n 5 92 116) matched on age and sex were enrolled in a cohort and all cases of SAB were registered. IRs and risk factors were estimated using time-updated Poisson regression analysis. ResultsWe identified 329 cases of SAB in 284 individuals, of whom 132 individuals were infected with HIV and 152 were not [crude IR ratio (IRR) 24.2; 95% confidence interval (CI) 19.5-30.0, for HIV-infected vs. non-HIV-infected individuals]. Over time, IR decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
1
15
0
4
Order By: Relevance
“…However, Larsen et al found that incidence of S. aureus infections among HIV-infected individuals declined but remained higher than that among HIV-uninfected individuals. S. aureus infection was more common among injecting drug users and patients with low CD4 cell counts [20]. S. epidermis was detected in 15.1% of our cases; all of them originated from blood isolates.…”
Section: Discussionmentioning
confidence: 63%
“…However, Larsen et al found that incidence of S. aureus infections among HIV-infected individuals declined but remained higher than that among HIV-uninfected individuals. S. aureus infection was more common among injecting drug users and patients with low CD4 cell counts [20]. S. epidermis was detected in 15.1% of our cases; all of them originated from blood isolates.…”
Section: Discussionmentioning
confidence: 63%
“…Among HIV-infected individuals, a low CD4 count was independently associated with SAB. Also, compared to injection drug users (IDUs), men who have sex with men (MSM) were likely to have a low CD4 count and to have nosocomial SAB (35). Thus, HIV-infected IDUs tend to acquire community-onset SAB as a consequence of injection drug use, whereas MSM have higher rates of nosocomial SAB.…”
Section: Epidemiologymentioning
confidence: 99%
“…Two studies reported incidences of SAB in HIVinfected patients of 494 per 100,000 person-years (35) and 1,960 per 100,000 person-years (36), or 24 times that of the non-HIVinfected population (35). Although much of this increase results from high rates of injection drug use in the HIV-infected population, even the non-injection drug-using HIV-infected population exhibits higher rates of SAB than those in the non-HIV-infected population (35). Among HIV-infected individuals, a low CD4 count was independently associated with SAB.…”
Section: Epidemiologymentioning
confidence: 99%
“…AIDS secondary to HIV is one of the most common cell-mediated acquired immune deficiency states worldwide (159). The incidence of SAB among HIV-infected individuals remains higher than that among individuals not infected with HIV (25,124,138,159,260,295). This risk is directly associated with the degree of immune deficiency, with the relative risk being 31 times higher (incidence rate ratio [IRR], 31.1; 95% CI, 10.3 to 94.0) for patients with CD4 cell counts of Ͻ100 cells/l than for patients with CD4 cell counts of Ն350 cells/l (159).…”
Section: Immune Statusmentioning
confidence: 99%